Homecoming 2013: decorating contest action underway - Uribes, Tom::::::::: (2013)
Homecoming fever ramps up at Fresno State today with seven university offices competing to win the annual Fresno State Staff Assembly Homecoming Office-Decorating Contest in the spirit of this year's 'throwback' homecoming theme.